SISTEM PENUNJANG KEPUTUSAN UNTUK MENENTUKAN PENERIMA BEASISWA PENINGKATAN PRESTASI AKADEMIK DI UNIVERSITAS TARUMANAGARA (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
The distribution of scholarship sometimes is not relevant. The main cause of this problem is because the selection process of the scholarship awardee is not using the right method and tools. The purpose of this research is to develop a decision support system to determine the Peningkatan Prestasi Akademik scholarship (PPA Scholarship) awardee using a few criteria from Students and Alumni Directorate. The methods that are being used is Simple Additive Weighting (SAW). A few criteria that are being used in this system are GPA score, student’s total credit, parents earning, and student’s achievement. The calculation using SAW methods have increase the speed and accuracy in determining the right scholarship awardee.